Assessment of exogenous geological hazards in Moscow, Russia - Eremina, Olga; Kozliakova, Irina; Anisimova, Nadezhda; Kozhevnikova, Irina (Journal of Nepal Geological Society, 2018)
Exogenous geological processes are exerting a significant impact on urban geo environment in Moscow endangering both surface and subsurface constructions. For surface construction, the principle geohazards in Moscow are karst-suffosion sinkholes, land subsidence, landslides, and waterlogging. The subsurface construction is endangered by karstification and fracturing of limestone, decompaction and swelling of clay, quicksand phenomena, and groundwater breakthrough to tunnels. Different methods are applied to study geohazards depending on the purpose and the scale of study. At the preliminary investigation stage, small-scale mapping and zoning of city surface or subsurface appears to be the most appropriate for the qualitative assessment of the risk of economic losses caused by exogenous geohazards. Assessment of the geological risk in Moscow was carried out separately for already existing urban infrastructure and for future planned construction. For existing surface urban infrastructure, geological risk is considered to be an integral parameter of probable damage caused by geohazards and the anthropogenic load on the specific territories. The main aim of risk mapping in this case is outlining the territories, for which restrictions and prohibitions should be imposed for further urban engineering development. For future subsurface urban construction, the risk-analysis consists in assessing the impact of geohazards on the engineering structure by comparing the future expenditures for the construction and operation under different engineering geological conditions. The risk maps in this case will help planners to compare and make alternative project decisions in order to minimize the cost in future economic expenditures. Both approaches are successfully approved in this investigation in Moscow.